A C-coated and Sb-doped SnO2 nanocompsite with high surface area and low charge transfer resistance as ultrahigh capacity lithium ion battery anode. (September 2019) - Zhang, Qiang; Gao, Qiuming; Qian, Weiwei; Zhang, Hang; Tian, Weiqian; Li, Zeyu
Abstract: A novel kind of C-coated and Sb-doped SnO2 (ATO/C) nanocomposite is prepared by a facile hydrothermal method following with high-temperature pyrolysis. The ATO/C particles are uniform, irregular, crystalline and small sizes (∼5–8 nm). High specific BET surface area of 192.1 m 2  g −1 and low charge transfer resistance of 98.9 Ω are obtained for the ATO/C. When used as the anode of lithium ion battery, the ATO/C shows an ultrahigh lithium storage capacity. It may deliver an initial discharge specific capacity of 2634.9 mAh g −1 with the Coulombic efficiency of 88.4% at 0.1 C, and the capacity increases to the highest 2847.4 mAh g −1 after 50 cycles. Even after 1000 cycles at the increased current density of 1 C, the discharge capacity of 1008.5 mAh g −1 can be preserved indicating its high cyclic stability. Besides, it has a capacity of 370.8 mAh g −1 at the higher current density of 10 C, exhibiting the robust rate property. Graphical abstract: Image 1 Highlights: A novel C-coated and Sb-doped SnO2 nanocompsite (ATO/C) is prepared. The ATO/C has high surface area and low charge transfer resistance. The ATO/C shows the highest capacity of 2847.4 mAh g −1 after 50 cycles at 0.1 C. The ATO/C presents a capacity of 1008.5 mAh g −1 after 1000 cycles at 1 C.